SUN-183 Adrenalitis Induced by Nivolumab - Khan, Muhammad Atique Alam (J Endocr Soc, 2020)
Introduction: Tumor cells often express a programmed death-ligand 1 (PD-L1), which binds to the programmed death receptor-1 (PD-1) on activated T-cells to induce immune tolerance. Among the class of immune checkpoint inhibitors (ICI), Nivolumab is an anti-PD-1 antibody which blocks these tumor cell interactions. Although some endocrinopathies have been reported for other PD-1 inhibitors, the adverse event of adrenalitis with nivolumab has not been reported before. Clinical Case: A 65-year-old female presented to the hospital with complaints of nausea, vomiting, fatigue, and headache for five days. She was recently diagnosed with metastatic lung adenocarcinoma, complicated by cerebellar metastases, and the left cerebellar mass was resected. She was also started on Nivolumab. Her blood pressure was 98/65 mmHg on the presentation. Serum sodium was 122mEq/L (normal 135–145) and potassium was 5mEq/L (3.5–5). TSH, LH, and prolactin were all normal. Aldosterone was low: 23pmol/L (27.7–582.5) and renin was high: 11 ng/ml/h (0.167- 1.38). Morning cortisol levels were low: 2.2 ug/dl (5- 25) and concomitant ACTH was high: 78 pg/ml (7.2- 63.3). Upon standard high dose cosyntropin stimulation test, basal cortisol was 2.0 ug/dl (5- 25). Cortisol level 30 minutes post cosyntropin was 7.1 ug/dl, while Cortisol 60 minutes post cosyntropin was 12.2 ug/dl (normal >18 -20 ug/dl). Considering the low cortisol levels with high ACTH, and an inadequate rise in cortisol after the ACTH stimulation test, adrenal insufficiency was suspected as a result of adrenalitis due to Nivolumab. Hyponatremia along with low aldosterone and high renin levels also reinforced this clinical diagnosis. A computerized tomographic scan of the chest abdomen and pelvis only showed calcified uterine fibroids. She was initially resuscitated with intravenous fluids. Hydrocortisone 100 mg every 8 hours was started and then gradually tapered down to 60mg every 12 hours. Fludrocortisone was also initiated at 0.2mg daily. Symptoms began to improve, and sodium levels normalized to136 mEq/dl. She was discharged on 30mg of hydrocortisone and 0.1 mg of fludrocortisone daily and is stable since then. Conclusion: This is a rare case of Nivolumab-induced adrenalitis. It highlights the importance of checking for adrenal insufficiency in a patient who presents with symptoms of hypotension and hyponatremia while being on ICI drugs, as unidentified adrenal insufficiency and adrenal crisis can be fatal.